2015
DOI: 10.1002/jor.23036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laminin‐A4 inhibition on cluster formation of human osteoarthritic chondrocytes

Abstract: Formation of chondrocyte clusters is not only a morphological sign of osteoarthritis but it is also observed in cell culture. Active locomotion of chondrocytes is controlled by integrins in vitro. Integrins bind to Laminin-A4 (LAMA4), a protein that is highly expressed in vivo in clusters of hypertrophic chondrocytes. We tested if LAMA4 is relevant for cluster formation. Human chondrocytes were cultured in a 2D matrigel model and treated with different concentrations of a monoclonal inhibitory anti-LAMA4-antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(98 reference statements)
1
5
0
Order By: Relevance
“…The colocalisation of CD146 and LAMA4 in the current study further reinforces the putative ligand-receptor interaction that CD146 and LAMA4 share, which has been demonstrated in previous studies [49,50]. In chondrocytes, blockading LAMA4 inhibited cluster formation, which is typical of pathological cartilage, and also resulted in downregulation of Claudin-1 (previously identified as a tendon IFM protein) and MMP3 [51,52]. Recent studies have already established that loss of LAMA4 results in reduced CD146 cell expression and loss of basement membrane/niche maintenance in both mesenchymal and haematopoietic environments [53].…”
Section: Discussionsupporting
confidence: 90%
“…The colocalisation of CD146 and LAMA4 in the current study further reinforces the putative ligand-receptor interaction that CD146 and LAMA4 share, which has been demonstrated in previous studies [49,50]. In chondrocytes, blockading LAMA4 inhibited cluster formation, which is typical of pathological cartilage, and also resulted in downregulation of Claudin-1 (previously identified as a tendon IFM protein) and MMP3 [51,52]. Recent studies have already established that loss of LAMA4 results in reduced CD146 cell expression and loss of basement membrane/niche maintenance in both mesenchymal and haematopoietic environments [53].…”
Section: Discussionsupporting
confidence: 90%
“…It has also been reported that LAMA4 is greatly increased on tumor blood vessels in colorectal and renal malignancies [23]. Furthermore, the overexpressed LAMA4 has been observed in vivo in clusters of hypertrophic chondrocytes, and it has been demonstrated to be associated with cellular motility and migration [24]. Zhi-Xue Yang et al demonstrated that LAMA4 expression elevated in triple-negative breast cancer tissues (TNBC), and the downregulated LAMA4 can suppress the proliferation, migration, and invasion of TNBC cells [25].…”
Section: Discussionmentioning
confidence: 90%
“…The five genes most related to ADAMTS5 were ADAM metallopeptidase with thrombospondin type 1 motif 1 (ADAMTS1), fibrillin 1 (FBN1), laminin alpha 4 (LAMA4), protocadherin 18 (PCDH18), and decorin (DCN). LAMA4-integrin signaling contributes to clustering in human osteoarthritic chondrocytes, which is a morphological sign of OA (17). Figure 2 shows the GO enrichment results of these genes.…”
Section: Resultsmentioning
confidence: 99%